CORRELATION BETWEEN STUDENTS' MENTAL READINESS AND MOTIVATION IN HAVING OFFLINE LEARNING IN THE POST-PANDEMIC ERA - Bilal, Buya Ahmad; Jabu, Baso; Talib, Ahmad (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
This study aims to determine whether there is a relationship between mental readiness and learning motivation of English Education students at Universitas Negeri Makassar. This research method is quantitative and uses correlation. The instrument used is a questionnaire using a Likert scale as an assessment analysis, which uses a scale of mental readiness and learning motivation. In this study, the questionnaire was distributed using Google Forms, and the analysis technique used was descriptive analysis. In this study, there is a correlation between mental readiness with offline learning motivation in the post-pandemic era 2021-2022 students of English education at Universitas Negeri Makassar. This is because the subject matter is relevant to students' affective, cognitive, and psychomotor mental readiness. The ability to restrain one's emotions so that they do not explode and ultimately impact reasonable behaviour is referred to as emotional management. Keywords – Mental Readiness, Learning Motivation